Motivos para a prática da corrida de rua e sua influência na satisfação com a vida - Barros Filho, Marcos Antonio (Educación Física y Ciencia.)
The aim of this study was to analyze the influence of motivations for running practice on the life satisfaction of amateur runners. The study is characterized as a quantitative research. The data collection procedure adopted was the E-survey, where individuals were invited through social networks to answer an online survey form available on the Google Drive platform. The sample consisted of 158 runners. The instrument used was a questionnaire composed of: (i) motivations; (ii) life satisfaction; (iii) running profile (iv) characterization of demographic data. The data were analyzed using the SPSS Statistics 24 software. The analysis of the predictive value of the independent variables resulted in a statistically significant model (F (3, 154) = 13.06; <0.001; R² = 0.20). Specifically, the social factor exerted the strongest influence (β = 0.325), followed by entertainment (β = 0.198). As a conclusion, the motivations for running practice prove to be significant factors for life satisfaction.